FERNÁNDEZ-ROJO, D., EU Migration Agencies. The Operation and Cooperation of FRONTEX, EASO and EUROPOL, Edward Elgar Publishing, Cheltenham, 2021, 254 pp. - Acosta Sánchez, Miguel (PEACE & SECURITY-PAIX ET SÉCURITÉ INTERNATIONALES (EuroMediterranean Journal of International Law and International Relations), 2026)
Reseña de: FERNÁNDEZ-ROJO, D., EU Migration Agencies. The Operation and Cooperation of FRONTEX, EASO and EUROPOL, Edward Elgar Publishing, Cheltenham, 2021, 254 pp.